Long-term survival follow-up for tebentafusp in previously treated metastatic uveal melanoma - Sacco, Joseph J.; Carvajal, Richard D.; Butler, Marcus O.; Shoushtari, Alexander N.; Hassel, Jessica C.; Ikeguchi, Alexandra; Hernandez-Aya, Leonel; Nathan, Paul; Hamid, Omid; Piulats, Josep M.; Rioth, Matthew; Johnson, Douglas B.; et al. (Journal for ImmunoTherapy of Cancer, 2024)
Background Tebentafusp, a bispecific (gp100×CD3) ImmTAC, significantly improved overall survival (OS) outcomes for HLA-A*02:01+ adult patients with untreated metastatic uveal melanoma (mUM) and showed promising survival in previously treated mUM with 1-year OS of 62% in the primary analysis of study IMCgp100-102. Here we report long-term outcomes from this phase 1/2 study in pretreated mUM. - Patients and methods Patients with previously treated mUM received tebentafusp weekly intravenous at 20 µg dose 1, 30 µg dose 2 and either 54, 64, 68, or 73 µg (phase 1) or 68 µg (phase 2) dose 3+. The primary objective was overall response rate. Secondary objectives included OS and safety. OS was estimated by Kaplan-Meier methods. Association between OS and baseline covariates, on-treatment Response Evaluation Criteria in Solid Tumors (RECIST) response, baseline tumor biopsy and circulating-tumor DNA (ctDNA) changes were assessed. - Results 146 patients were treated with tebentafusp: 19 in phase 1 and 127 in phase 2. With a median follow-up duration of 48.5 months, the median OS was 17.4 months (95% CI, 13.1 to 22.8), and the 1-year, 2-year, 3-year and 4-year OS rates were 62%, 40%, 23% and 14%, respectively. Improved survival was associated with lower ctDNA baseline levels and greater ctDNA reductions by week 9 on-treatment, with 100% 1-year, 73% 2-year and 45% 3-year OS rates for patients with ctDNA clearance. Baseline gp100 expression was not associated with survival, despite more RECIST responses among patients with higher expression. No new safety signals were reported with long-term dosing. - Conclusions This study represents the longest follow-up of a Tcell receptor bispecific to date and confirms the durable survival benefits achieved with tebentafusp in previously treated mUM with good tolerability long-term. A role for ctDNA reduction as an early indicator of clinical benefit was again suggested for patients treated with tebentafusp.
Gesehen am 09.12.2024